Modeling growth rates and anomalies of financing, investment and dividend decisions. (3rd July 2018) - Eldomiaty, Tarek Ibrahim; Bahaa El Din, Mohamed; Atia, Ola
Abstract: As far as uncertainty is prevalent, financial anomalies increase the complexity of financial decisions. The possible consequence of an anomaly is either an over or underreaction. This paper suggests that the use of mathematical programming can lessen the degree of complexity when planning for financing, investment and dividend decisions. The authors develop a comprehensive form of the External Financing Needed model in order to show the generic and combined relationship among the three financial decisions. The comprehensive model shows nonlinear relationships between the three financial decisions. The paper uses a simulated numerical example to illustrate how financial objective functions (e.g. targets) can be set out under certain constraints. The latter serve as a remedy for financial anomalies. The results show that financing, investment and dividend decisions can be made optimally to serve having consistent financial statements.